Supply and Demand of Rice in Indonesia: A Critical Review - Sri Herliana; Sudrajati Ratnaningtyas; Qorri Aina; Umi Zuraida; Acip Sutardi; Syifaya Qorina (AIBPM Publisher, 2025)
The demand and supply of rice as a staple food is a crucial factor in the food supply chain and food security in Indonesia. Indonesia still faces a deficit in domestic rice supply, which leads the government to adopt import policies to fill this shortage. Therefore, there is a need to understand the dynamics of rice supply and demand, as the interaction between the two is complex, to address food security concerns. This research aims to critically assess the dynamics of rice supply and demand in Indonesia, highlighting the key challenges and opportunities to improve food security. Using a critical review methodology, the study analyzes and critiques recent linear studies, literature, government policies, and statistical data to highlight their strengths, weaknesses, and challenges, providing a comprehensive understanding of the rice production supply and demand. The conclusion of this research is that a holistic approach is needed to achieve food security. The findings suggest that Indonesia must implement a comprehensive approach, incorporating environmental, political, and socioeconomic factors in food security. Future research should explore the role of climate resilience and global trade dynamics in shaping Indonesia’s rice sector. This comprehensive perspective can help decision-makers create a more sustainable food system